A Critique of Manz's Epistemological View on the Book “Power, Politics and Religion in Timurid Iran” - Sayyed Abolfazl Razavi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
This present paper criticizes the interpretive approaches of Beatrice Forbes Manz’s, a researcher of Mongol and Timurid era, on the book "Power, Politics and Religion in Timurid Period in Iran". Manz survey “Shahrokh's Era History” and specially relations between society and government by different viewpoints and come up with new horizons. Thus, after introducing each chapter briefly about the Timurid surveying arena, it criticizes epistemological basics and author’s model theory through which the author interprets relations between society and government. The mentioned criticisms honor author’s viewpoint in coming up with new horizons in Timurid historiography, provoke readers to see Timurid’s successor’s  society and government’s structure in a different way, pay attention to her attitude about Shahrokh Era History.